A new hire's dilemma: reporting corruption. Issue 3 (12th September 2016) - Zouharis, Laurie
Abstract : Synopsis: Bill Edwards, a newly hired Accounts Payable Manager at Nicalmic Ltd, has noticed that his boss, the company controller, changed data in the vendor master record, while he was a contractor in the interim role, to prevent his income from being reported to the IRS. How should Bill handle this knowledge? Research methodology: This is a disguised field-researched case. Relevant courses and levels: This case may be used in a variety of undergraduate business courses, such as introduction to business, business ethics, business law and ethics and freshman seminar. Theoretical bases: Students should have some understanding of business ethics, ethical decision making and risks to employees who report unethical conduct.